Tracking and coupled dark energy as seen by the Wilkinson Microwave Anisotropy Probe - Amendola, Luca; Quercellini, Claudia (Physical review. D, Particles, fields, gravitation, and cosmology, 2003)
The satellite experiment, the Wilkinson Microwave Anisotropy Probe (WMAP), has produced for the first time a high-coverage, high-resolution survey of the microwave sky, releasing publicly available data that are likely to remain unrivaled for years to come. Here we compare the WMAP temperature power spectrum, along with an exhaustive compilation of previous experiments, to models of dark energy that allow for a tracking epoch at the present, deriving updated bounds on the dark energy equation of state and the other cosmological parameters. Moreover, we complement the analysis by including a coupling of the dark energy to dark matter. The main results are (a) the WMAP data alone constrain the equation of state of tracking dark energy to be wφ<−0.67(−0.49) to 68%(95%) (confining the analysis to wφ>−1), which implies for an inverse power-law potential an exponent α<0.99(2.08), and (b) the dimensionless coupling to dark matter is |β|<0.07(0.13). Including the results from supernovae type Ia further constrains the dark energy equation of state.
Gesehen am 17.11.2017